Sr doped TiO2 photocatalyst for the removal of Janus Green B dye under visible light - Keerthana, Subramanian P. (2024)
Hydrothermal synthesis of pristine and Sr doped TiO2 is proposed. The synthesized products were studied for their physiochemical properties. 3% Sr-TiO2 showed a narrow bandgap, which facilitate an increase in oxygen vacancies. The agglomerated morphology was tuned to a nanoball structure after doping with Sr ions. Surface area was increased for the Sr doped TiO2. The samples were used to reduce Janus Green B (JG) dye as a model pollutant. The pure TiO2 showed poor efficiency, while the prepared Sr-TiO2 photocatalyst showed enhanced efficiency with a corresponding increase in the rate constant values of the samples. Tuning of the bandgap, an improvement in the morphology and an increase in the surface area were the major positives of the Sr doped TiO2 samples compared to pure TiO2, 3% Sr-TiO2 is emerging as the best photocatalyst in reducing toxic pollutants. The 3% Sr-TiO2 is a promising candidate for water remediation in the future.